The living social between the ethics and the pluralism: "a perspective from Emmanuel. Lévinas" - Calderón C., Antonio (2018)
In general, terms, the present essay approaches the understanding of the phenomenon of social coexistence under two very relevant edges that are the pluralism and the ethics of the citizens. In particular, it tries to understand the possibility of living together and the main features that help people to know how to be next to each other. It also discusses and dialogs with some characteristics of the approach that performs Emmanuel Lévinas, especially the very relevant elements of his thought as: dialog, responsibility, justice, freedom, respect (tolerance). The social coexistence of today is a challenge, for the many demands that the human being has been imposed today under a scenario of a lot of diversity. Finally, in the reflections it is argued the importance of openness and search of living with another people to enhance a life of citizenship and with its back to understand ourselves as human beings and to forge a humanity with a sense. Humanity that Lévinas presents as the first ethic.